DIGITALIZATION AND INFORMATION SUPPORT FOR INNOVATION ACTIVITIES - Denchyk, Iryna; Petrykiva, Taisiia (Collection of scientific papers «ΛΌГOΣ», 2024)
The digitalization of society has brought transformative changes across industries, enabling faster access to information, streamlined processes, and enhanced communication. For businesses and institutions engaged in innovation, the digitalization of society provides vast opportunities to enhance information support systems, facilitating the efficient collection, analysis, and dissemination of data essential for innovation [1]. This presentation explores the opportunities presented by digitalization to support innovation, discussing the role of digital infrastructure, data accessibility, and emerging technologies. It also examines the challenges and considerations for harnessing digital tools effectively within the information ecosystem that drives innovation.